Perfil de la demanda turística del cantón Pangua, provincia de Cotopaxi año 2021 - Bautista Andino, Andrés Marcelo (2021)
This research project was carried out with the purpose of knowing the "profile of the tourist demand of the Pangua canton, through descriptive research with a qualitative approach through the application of surveys, which are subject to measurement, statistical analysis and verification of the same. In the first objective, the inductive method was applied in order to collect and analyze the information of the tourists who visit the canton. To carry out this research, the inductive method was applied, which allows a first analysis and obtain primary and secondary information; Through the compilation of bibliographic documents such as theses, books, virtual documents and the PDOT (Development and Territorial Planning Plan) of the Pangua canton. In which the study area was identified, in this way it was possible to identify that the canton has certain natural and cultural places such as Angamarca la Vieja, Piedra de la Cruz, Churo Pucará, "Rancho Escondido" Eco-Tourist Complex, Aguas Calientes, The Seven Waterfalls of Zapanal, the latter being the attraction with the most tourist influx. In the second objective, field research was applied, through the application of surveys, research instruments that allow data collection. A questionnaire was elaborated, a pilot test was applied to validate results. Once the tourist attractions with the greatest influx of people had been determined and the information collection instrument established, the sample size was calculated using the non-probabilistic sampling formula that concluded a total of 385 surveys, these being applied in the places with the highest tourist influx of the canton. In the third objective, quantitative research was applied, which allows us to collect data and make use of mathematical tools, statistics and information to measure the results. Once the information was collected, the results were tabulated, analyzed and interpreted, thus revealing that the 385 surveyed tourists who visit the Pangua canton are 100% national tourists, revealing that the lower limit of local tourists is 45.53% while 56.81% belong to the upper limit who opt for nature and adventure tourism, their preferred activities are walking, swimming and sports, their diet is based on the typical foods of the place and preferably they like to travel with family or groups of friends. The purpose of this research was to analyze the profile of the tourist demand of the sample to be tabulated (385 tourists) who visit the Pangua canton, making use of different study elements, for this, the identification of the type of visitor, place of origin and tourist behavior in the areas: demographic, socio-economic, motivation and preference; variables of great contribution to determine the profile of the tourist, with the aim of publicizing the most representative places that the canton has and generating economic income to its inhabitants who have been affected by the pandemic (Covid 19).